Régimenes políticos y sujetos - Forace, Virginia P. (Verba hispanica, 2014)
The accounts of D. F. Sarmiento%s journey to Europe and USA have attracted the attention of literary critics since their publication because of the political project that they proposed and their exceptional rhetorical construction. His project responded to a major concern of the Río de la Plata intellectuals: the creation of a new country and the inauguration of a new political phase of order and progress which would put an end to Argentinian political instability. The answer to this question lays for Sarmiento in the study and importation of European society models. However, while he was travelling through Europe, he experienced a change in his perspective and he started to look to North American society. This change is the main point of interest of this paper in which the author proposes a discursive analyses of how that change is expressed in two letters: "Paris", sent on September 4th of 1846 - at the beginning of his travenl - and "USA", sent on November 12th of 1847 - his last stop. In the last letter Sarmiento also proposes a new society model, the North American one, and tries to persuade the reader, with rhetorical and argumentative means of the adequacy of this model.
Keywords: Sarmiento, Domingo Faustino, 1811-1888; latinskoameriška književnost; United States of America; ZDA; Pariz; družbeni modeli; potopisi